Shock & Vibration, Aircraft/Aerospace, Energy Harvesting, Acoustics & Optics, Volume 9 Proceedings of the 34th IMAC, A Conference and Exposition on Structural Dynamics 2016 - Brandt, Anders; Singhal, Raj (Conference Proceedings of the Society for Experimental Mechanics Series, 2016)
Shock Vibration, Aircraft /Aerospace, Energy Harvesting, Acoustics Optics, Volume 9. Proceedings of the 34th IMAC, A Conference and Exposition on Dynamics of Multiphysical Systems: From Active Materials to Vibroacoustics, 2016, the ninth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early fi ndings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on: < • Energy Harvesting • Adaptive Support • Shock Calibration • Operating Data Applications • Aerospace Testing Techniques • Aircraft /Aerospace Applications • Joints • Acoustics & Optics • Other Sensing.